Depth Prediction of Karstic-Fault Reservoirs Based on Wellbore Temperature Measurements and Numerical Simulations. (22nd June 2020) - Lei, Jian; Pan, Baozhi; Guo, Yuhang; Fan, YuFei; Zhang, Lihua
Abstract : Karstic-fault oil pools are a new type of carbonate reservoirs which is consisted of groups of large caves with high oil storage potential. In this study's examinations of high-yielding wells, it was found that many valuable reservoirs relate to the drilling wells through fractures or karst caves, and it was not possible to determine the reservoir depths through the method of seismic prospecting precisely due to its poor vertical resolution. The conventional logs cannot be run in the case of no mud circulation due to leaking to the caves. If the depths of the reservoirs cannot be determined, then it becomes difficult to achieve long term and stable development of the oil resources in the reservoirs. The heat transfer between wellbore and formation during oil production processes was simulated by CFD. The Horner method was used for estimating the flow temperature during the stable production stage using the temperature curve measured after shut-in. This research presented a scheme which could be used to effectively determine the depths of karstic-fault reservoirs by static and flow temperature logs. The proposed method was applied to a well located in the Tahe Oilfield of the Tarim Basin. The application of the method will aid in deepening our understanding of the distribution of fault-karst reservoirs, as well as in supporting the future stable and sustainable high-yielding oilfield production of similar reservoirs.